Biotechnological crops under the biosecurity framework - Rodríguez Chalarca, Jairo (Revista Colombiana de Investigaciones Agroindustriales, 2014)
With the approval and release of the biotechnological cotton during 2002 inColombia, a series of questions have been generated about the appropriatenessor not of its incorporation in tropical agricultural systems. Among all the concerns that genetically modified crops (GMC) may arise are: (i) The possible impact onthe technology’s non target organisms (parasitoids, predators, pollinators). (ii) loss of susceptibility under field conditions of the pest populations, target of the different technologies commercially released in Colombia. The introduction, release and marketing of these crops in Colombia, are marked in the Cartagena Protocol on Biosafety as an international instrument regulating living modified organisms (LMO) resulting from modern biotechnology. With the purpose of responding to concerns related with the susceptibility of the pests, target of the different technologies in Colombia, the National Biosafety Technical Committee, considered to be a high priority to establish a susceptibility monitoring program to “Cry” and “Vip” proteins. The information over the impact of GMC on pests target of Colombian technology can be instantiated with studies on Spodoptera frugiperda that indicate the sub-lethal effects as an indirect effect of the material consumption that express Biotechnological Insecticidal proteins. The studies involve parameters such as: (i) percentage of weight compared with the control, (ii) demographic parameters among others. Aspects that have led to the sub-lethal effects as a consequence of antibiotic mechanism of GMC. Para citar este artículo Rodríguez, J. (2014). Cultivos biotecnológicos en el marco de la bioseguridad. Revista colombiana de investigaciones agroindustriales, 1(1), 94-102. DOI: http://dx.doi.org/10.23850/24220582.120